Pengaruh Erosivitas Hujan yang Diperoleh dari Rumus yang Berbeda terhadap Pemodelan Erosi Berbasis Raster (Studi Kasus di DAS Merawu, Banjarnegara, Jawa Tengah) - Bambang Sulistyo (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2011)
The research aims at studying the efect of rain erosivity generated from different formulae on a fully raster-based erosion modeling of USLE (Universal Soil Loss Equation) with the support of remotely sensed data of Landsat 7 ETM+ and geographical information system technique. Methods applied were by analysing all factors affecting erosion in GIS environment. Monthly R factor was evaluated based on formula developed by Abdurachman, Bols, Lenvain, Soemarwoto and Utomo using rainfall data recorded between June 2004 and May 2006. K factor was determined using modified formula used by Department of Forestry based on the result of laboratory analysis from 30 soil samples taken in the field. LS Factor was derived directly from DEM (Digital Elevation Model) and by taking flow direction from each pixel into consideration. C factor was derived from the formula after applying regression analysis between NDVI (Normalized Difference Vegetation Index) of Landsat 7 ETM+ and C Factor measured directly on the field. P factor was derived from the combination betweenslope data from DEM and landcover classification interpreted from Landsat 7 ETM+ using criteria developed by Abdurachman. Another analysis supporting the research activity was the creation of Map of Bulk Density used to convert erosion unit as from ton/hectare/month to mm/month. After all erosion parameter were analysed, then erosion can be calculated by using R Factor using different formulae. To know its effect, erosion obtained from the model (E ) were compared with actual erosion (E ) measured regularly at outlet of the Merawu watershed. Comparison was done by using Correlation Analysis and Direct Comparison. The research result showed that fully raster-based erosion modeling of USLE (E ) using rain erosivity developed by Abdurachman has high coefficient of correlation (r = 0.873) with E and resulted high accuracy (i.e. 81.13 %).ABSTRAKPenelitian ini bertujuan untuk mengkaji pengaruh erosivitas hujan yang diperoleh dari rumus yang berbeda terhadap pemodelan erosi USLE (Universal Soil Loss Equation) yang berbasis raster dengan memanfaatkan citra Landsat 7 ETM+ dan Sistem Informasi Geografis (SIG). Metode penelitian ini adalah melakukan analisis semua faktor yang mempengaruhi erosi dengan bantuan SIG. Faktor R dihitung menggunakan rumus yang dikembangkan oleh Abdurachman, Bols, Lenvain, Soemarwoto dan Utomo dari 8 stasiun curah hujan yang direkam dari Juni 2004 sampai Mei 2006. Faktor K dihitung, dari 30 sampel tanah yang diambil dan dianalisis di laboratorium, menggunakan rumus K yang sudah disesuaikan. Faktor LS diturunkan dari analisis DEM (Digital Elevation Model) dengan memperhatikan flow direction dari masing-masing piksel. Faktor C diturunkan dari hubungan NDVI (Normalized Difference Vegetation Index) citra Landsat 7 ETM+ dengan Faktor C yang diukur di lapangan. Faktor P diturunkan menggunakan kriteria yang dikembangkan oleh Abdurachman yaitu yang diperoleh dengan kombinasi data slope hasil turunan DEM dengan penutupan lahan yang diinterpretasi dari citra Landsat 7 ETM+. Analisis lainnya adalah penyusunan peta berat jenis tanah yang digunakan untuk mengkonversi satuan erosi dari ton/Ha/bulan menjadi mm/bulan. Setelah semua parameter erosi dianalisis, erosi kemudian dihitung dengan Faktor R menggunakan rumus yang berbeda. Untuk mengetahui pengaruhnya, erosi yang diperoleh dari model (E ) dibandingkan dengan erosi aktual yang terjadi (E ) yang diukur di DAS Merawu. Pembandingan dilakukan menggunakan Analisis Korelasi dan Pembandingan Langsung. Hasil penelitian menunjukkan bahwa hasil erosi model dengan USLE berbasis raster (E ) yang memanfaatkan erosivitas hujan menggunakan rumus Abdurachman mempunyai nilai koefisien korelasi yang tinggi (r = 0,873) dengan aktual dan sekaligus menghasilkan ketelitian yang sangat tinggi (yaitu 81,13 %).